Public debt and long-term interest rates: the case of Germany, Italy and the USA - Paolo Paesani; Rolf Strauch; Manfred Kremer (European Central Bank (ECB), 2006)
The debate on the sustainability of public finances is closely related to the analysis of the financial and macroeconomic consequences of government debt accumulation. Focusing on the USA, Germany and Italy over the 1983-2003 period, the central issue addressed in this paper is how the accumulation of government debt affects long-term interest rates, both nationally and across borders. The analysis is based on a small, multivariate econometric model, which allows us to disentangle the more permanent and transitory components of interest rate developments. Empirical evidence shows that in all cases a more sustained debt accumulation leads at least temporarily to higher long-term interest rates. This transitory impact also spills-over into other countries, mainly from the US to the two European countries.
Keywords: E6; H63; 330; cointegration; Common Trends; long-term interest rates; public debt; Öffentliche Schulden; Zinsstruktur; Kointegration; Deutschland; Italien; USA